Risks of malignancies related to disease-modifying antirheumatic drugs in rheumatoid arthritis: a pharmacovigilance analysis using the FAERS database - Xiong, Wan; Li, Yilin; Hu, Lin; He, Gefei; Huang, Juanjuan (Frontiers in Pharmacology, 2024)
Objectives: Over the years when disease-modifying anti-rheumatic drugs (DMARDs) have been used in rheumatoid arthritis patients, reports of malignancies have emerged. This study aims to investigate the association between malignancies and DMARDs by using data extracted from the Food and Drug Administration Adverse Event Reporting System (FAERS).Methods: FAERS data (January 2019 to December 2023) were reviewed. For each drug-event pair, the disproportionality analysis was conducted to evaluate the risk of malignancy. Multivariate logistic regression was implemented to mitigate potential biases. Moreover, the time to onset of malignancy was also evaluated.We conducted a detailed search for rheumatoid arthritis indications and identified a total of 17,412 adverse event reports associated with malignancies, with selective DMARDs designated as the role code "primary suspect". At the preferred term level, there were 198 positive signals, among which the lower limit of the 95% confidence interval for the information component is 3.55 for squamous cell carcinoma of the skin, 2.39 for breast cancer, and 2.27 for lymphoproliferative disorder. In comparison to other DMARDs, targeted synthetic DMARDs were associated with a broader range of malignancies at both preferred term and Standardized MedDRA Queries levels. The number of adverse events reported in female patients is approximately 2 to 3 times higher than men, and the median age across the population was approximately 62 years. In terms of onset time, the conventional synthetic DMRADs exhibited a relatively longer median time, ranging from 3.58 to 7.08 years, while the targeted synthetic DMARDs demonstrated a shorter median time of 0.83 to 1.67 years. Conclusion: Our study uncovers varying degrees of malignancy risks related to DMARDs, with a significantly higher risk observed in targeted synthetic DMARDs. Additionally, novel malignancy signals, not documented in product labels, have been detected. In the future, further research will be necessary to validate our findings.